PERTUMBUHAN TANAMAN KELAPA SAWIT DI LAHAN PASANG SURUT (Jurnal Pertanian Tropik, 2017)
Limitations of potential land for the palm oil industry in Indonesia led to the development ofmature oil palm plantations leads to marginal lands with various limiting factors. One ofthe marginal lands that could potentially as an alternative for palm oil development in the tidalwetlands. The potential of tidal land for oil palm cultivation is mainly related to the flattopography and water availability throughout the year to minimize the possibility ofwater deficit. However, there are some critical issues that become limiting for thedevelopment of oil palm plantations, which severely hampered drainage, high salinity,the potential content of pyrite, peat depth and maturity, as well as greater investment forinfrastructure development. Growth and productivity of oil palm trees in addition to tidalland affected by the improvement in the fertility rate are also influenced by watermanagement. The observation of vegetative ( leaf area ) of oil palm plantations age of 2years in a swamp area pitu ( pyrite 80-100 cm depth ) showed that the water managementin the water level of 20-40 cm had greater leaf area ( 2.93 m2 ) compared with watermanagement 0-20 cm ( 2.40 m2 ) and 40-60 cm ( 2.21 m2 ) below the ground surface.According to Winarna ( 2007), the productivity of oil palm plantations aged 10 years onacid sulfate soil in North Sumatra with water management and good pyrite can reach therange of 20-24 tonnes FFB /ha/year. The results of the observations made by Harahapand Siregar (2004 ) at the age of oil palm plantation in Betong Krawo 5-6 years ( depth of pyrite 50-100 cm ) with water management and pyrite are not maximized, which indicatesthat the low productivity range 10.86 - 12.70 tonnes FFB /ha/year.